Considerations on the meaning of organizational culture in a higher education institution - Quirós García, Elizabeth (2021)
This paper advocates to determine the concept of organizational culture in a higher education institution located in the great metropolitan area of Costa Rica. In order to achieve the goals proposed, the research was preeminently conducted under a positivist paradigm, working under a non-experimental quantitative method and cross-sectional descriptive study. Moreover, the premise that the organizational culture of a collectivity plays a vital role when proposing, implementing, developing, and consolidating actions and activities, being these academic and outreach cultural and teaching programs.